Effects of Cinnamon Bark Extract, Moderate Intensity Exercise, Intermittent Fasting, Metformin on Fasting Blood Glucose Levels, Lipid Profile and Malondialdehyde in DMT2 Rats: Case Study - Vonikartika, Arie (PT. Riset Press International, 2025)
Diabetes is a silent killer. Diabetes mellitus (DM) occurs when the pancreas does not produce enough insulin or the body cannot use insulin effectively. DM is often characterised by chronic hyperglycemia. Diabetes Mellitus (DM) is one of the Non-Communicable Diseases (NCDs), which is a public health problem and has a relatively high number of sufferers in the world. Many ways are used to treat and prevent DM, including changing to a healthier lifestyle and using modern medicine or herbal medicine that can improve hyperglycemia in DM patients. This study was conducted to determine the effects of cinnamon extract with a dose of 120 mg / kgBW / day orally, moderate swimming exercise, and intermittent fasting for 19 days on T2DM Rats. The study shows that there was a significant increase (p<0.005) in Fasting Blood Glucose (FBG) between day 1 and day 4 in the untreated group. In the group given metformin, there was a significant change in FBS on day 1 and day 4. In the group given cinnamon extract, there was a change in FBG on days 1 and 4 (increase) and days 10 and 13 (decrease). In the swimming group, there was an increase in FBG on day 1 and day 4 and a significant decrease in FBS on days 10 and 14, while in intermittent fasting, there was an increase in FBS on day 1 and day 4, which was statistically significant. Increases and decreases in lipid and Malondialdehyde (MDA) profiles were also present in each treatment group. The conclusion is that cinnamon bark extract, moderate-intensity swimming exercise, and intermittent fasting impact fasting blood glucose levels, lipid profiles, and MDA in Diabetes induced rats.